Question #2dc91

2 Answers
Feb 1, 2018

The third person will have to pay 1/6 of the cost.

Explanation:

Let the total cost be x
One of the three agrees to pay 1/2 x, and other agrees to pay 1/3x
So, the amount remaining to be payed will be:

x- 1/2x-1/3x

Equating the denominators:

= x (6/6) - 1/2 (3/3) x - 1/3 (2/2) x

= (6x - 3x - 2x)/6

= x/6

So, the third person will have to pay 1/6 of the cost.

Feb 1, 2018

1/6

Explanation:

"the total cost can be represented by "1

"adding the fractions "1/2+1/3

"the "color(blue)"lowest common multiple "" of 2 and 3 is 6"

rArr1/2+1/3=(1/2xx3/3)+(1/3xx2/2)=3/6+2/6=5/6

"third person has to pay "1-5/6=6/6-5/6=1/6

"third person pays "1/6" of the cost"